Regional employment generation potential of the Turkish labor market: an inter-sectoral perspective - Gündüz, Umut; Kaya, Tolga (Technological and Economic Development of Economy, 2017)
Contractionary effects of the current global crisis are not homogenous among sectors. Moreover, sectoral employment multipliers and high regional unemployment differentials unequally transfer these effects into labor market. The purpose of this study is to explore the inter-sectoral sensitivities of regional labor markets in Turkey to changes in the final demand. To do this, we decompose the labor demand by sectors and by regions using input-output methodology. Own employment generation effects and regional employment multipliers of each sector are calculated. Overall findings constitute an employment generation map of Turkey. One of the major findings is the strength of the mutual relationship between agriculture and manufacturing sectors. The biggest spillover effect is created by manufacturing upon mostly agriculture, trade and transportation. Agriculture, social services and trade are the most sensitive sectors to changes in the final demand. At regional level; trade, social services and manufacturing are the most influential sectors on Istanbul. Besides, agriculture, social services and construction sectors have the highest employment generation potentials in South Eastern Anatolia. First published online: 17 Apr 2015